Navigating Precarious Terrains: Reconceptualizing Refugee-Youth Settlement - Nunn, Caitlin; Gifford, Sandra M.; McMichael, Celia; Correa-Velez, Ignacio (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2017)
Settlement is widely understood as the final stage of the refugee journey: a durable solution to forced displacement and a stable environment in which former refugees can rebuild their lives. However, settlement is shaped by rapidly changing socio-political forces producing contingent, unpredictable, and even hostile environments. This article draws upon Vigh’s concept of social navigation to reconceptualize settlement as a continuation of a fraught journey in which refugee settlers must continually seek new strategies to pursue viable futures. We illustrate with an in-depth case study of the settlement journey of one refugee-background young man over his first eight years in Melbourne, Australia.